Illuminations - Benjamin, Walter; Arendt, Hannah (London : Pimlico, 1999)
- Walter Benjamin: 1892-1940 / Hanna Arendt ##- Unpacking my library: a talk about book collecting ##- The task of translator: an introduction to the translation of Baudelaire's Tableaux parisiens ##- The storyteller: reflections on the works of Nikolai Leskov ##- Franz Kafka: on the tenth anniversary of his death ##- Max Brod's book on Kafka: and some of my own reflections ##- What is epic theatre? ##- On some motifs in Baudelaire ##- The image of Proust ##- The work of arts in the age of mechanical reproduction ##- Theses on the philosophy of history.
Translated from the German Schriften, Suhrkamp, 1955
boek
Keywords: Benjamin, Walter; Arendt, Hannah